PEMERIKSAAN KADAR KALSIUM PADA MASYARAKAT DENGAN POLA MAKAN VEGETARIAN - Siti Nur Husnul Yusmiati; Erni Erni (Jurnal SainHealth, 2017)
Vegetarians are people consuming food derived from plants or processed products, such as milk and eggs. Cereals, pulses and results nuts, tofu, tempeh and green vegetables are good source of calcium as well, but these foods contain many substances that inhibit the absorption of calcium such as fiber, phytate and oxalate, so feared vegetarians are deficient in calcium.This study is to determine the levels of calcium serum in the vegetarian by using the Colorimetric Assay. This research was conducted at the Laboratory of Clinical Chemistry Faculty of Health Sciences, Maarif Hasyim Latif University, held on March 4, 2016 until April 18, 2016. The results of a study of 25 serum samples of the vegetarian, 4 samples (16%) showed the level of calcium in the normal range and 21 samples (84%) below the normal value. This research it can be concluded that the majority of the vegetarian’s serum calcium levels below the normal value.